PENGARUH TERAPI AL-QURAN SURAT ALI-IMRAN AYAT 139 UNTUK MENINGKATKAN KONSEP DIRI SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK DI SMA NEGERI 8 PEKANBARU - Hasanah, Nur; Umari, Tri; Yakub, Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of Al-Qur'an letter Ali-Imran verse 139 therapy through group guidance services on the self concept. This research was conducted at Pekanbaru State High School 8 from January to February 2019. The research method used was a quantitative method with one group pretest-posttest experimental research. The subjects of this study were students of class X IPA 6 with a low level of self-concept (negative) totaling 7 people. The instrument of data collection used was a questionnaire using a modified Likert scale. The data analysis technique used is the Non Parametric statistical technique using the Wilcoxon Test and the Spearman Rank Test. The results of the study show of students' self-concept before being given Al-Qur'an therapy letter Ali-Imran verse 139 through group guidance services, which is in the low category (71.43%) and moderate (28.57%), after being given Al-Qur'an therapy letter Ali-Imran verse 139 through group guidance services was in the high category (57.15%) and very high (42.85%). Based on the Wilcoxon Test there are significant differences in students' self-concept before and after Al-Qur'an therapy letter Ali-Imran verse 139 through group guidance services Based on the Spearman Rank Test it can be concluded that the relationship of Al-Qur'an therapy letter Ali-Imran verse 139 through group guidance services with self-concept of students in the high category 0.901 or 90%. Next to find out the following seabgai detemination coefficient: (rs)2 = (0.901)2 = 0.81. This means that the influence of Al-Qur'an letter Ali-Imran verse 139 therapy through group guidance services to improve students' self-concept is 81% while 19% is influenced by other factors outside the variables studied. Key Words: Al-Qur’an Therapy Letter Ali-Imran Verse 139, Self-Concept, Group Guidance